2017
DOI: 10.1002/jgf2.142
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status is associated with the return home in a long‐term care health facility

Abstract: BackgroundThe purpose of this study was to determine the association between nutritional status and the return home of older people living in a long‐term care health facility (LCHF).MethodsA nested case control study was performed in 116 people ≥65 years of age in a single LCHF. Nutritional status was assessed using the Mini Nutritional Assessment Short Form (MNA‐SF) and activities of daily living by the Functional Independence Measure (FIM). The return home, duration of rehabilitation, and the family wanting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…21 About 70% of older people living in long term care facilities are malnourished; malnutrition, and total FIM score, were independently associated with the time taken to return home. 22 Reports from literature confirm the findings of this study, demonstrating the benefits of nutritional support on rehabilitation outcomes in patients in the hospital and home care setting.…”
Section: Discussionsupporting
confidence: 86%
“…21 About 70% of older people living in long term care facilities are malnourished; malnutrition, and total FIM score, were independently associated with the time taken to return home. 22 Reports from literature confirm the findings of this study, demonstrating the benefits of nutritional support on rehabilitation outcomes in patients in the hospital and home care setting.…”
Section: Discussionsupporting
confidence: 86%
“…4 During the early period of a patient's stay in a neurointensive care unit (neuro-ICU) or stroke care unit (SCU) after acute stroke onset, nutritional management is reportedly critical to prevent malnutrition and poor functional recovery. 5,6 Another study also showed that proper energy intake is independently associated with improvement in ADL 6 and reduction in the mortality rate. 7 However, the proper amount of energy to prevent adverse events during the early period after stroke has not been studied.…”
Section: Introductionmentioning
confidence: 96%